Validity of SenseWear® Armband v5.2 and v2.2 for Estimating Energy Expenditure - Bhammar, Dharini M (J Sports Sci, 2016)
We compared SenseWear Armband versions (v) 2.2 and 5.2 for estimating energy expenditure in healthy adults. Thirty-four adults (26 women), 30.1±8.7 years old, performed two trials that included light-, moderate-, and vigorous-intensity activities: 1) Structured routine: Seven activities performed for 8-min each, with 4-min of rest between activities; 2) Semi-structured routine: 12 activities performed for 5-min each, with no rest between activities. energy expenditure was measured by indirect calorimetry and predicted using SenseWear v2.2 and v5.2. Compared to indirect calorimetry (297.8±54.2 kcal), total energy expenditure was overestimated (P<0.05) by both SenseWear v2.2 (355.6±64.3 kcal) and v5.2 (342.6±63.8 kcal) during the structured routine. During the semi-structured routine, total energy expenditure for SenseWear v5.2 (275.2±63.0 kcal) was not different than indirect calorimetry (262.8±52.9 kcal), and both were lower (P<0.05) than v2.2 (312.2±74.5 kcal). Average mean absolute percent error was lower for the SenseWear v5.2 than for v2.2 (P<0.001). SenseWear v5.2 improved energy expenditure estimation for some activities (sweeping, loading/unloading boxes, walking), but produced larger errors for others (cycling, rowing). Although both algorithms overestimated energy expenditure as well as time spent in moderate-intensity physical activity (P<0.05), v5.2 offered better estimates than v2.2.